The odd women - Gissing, George, 1857-1903 (Oxford world's classics (Oxford University Press), 2000)
Set in grimy, fog-ridden London, these `odd' women range from the idealistic, financially self-sufficient Mary Barfoot and Rhoda Nunn, who run a school to train young women in office skills for work, to the Madden sisters struggling to subsist in low-paid jobs and experiencing little comfort or pleasure in their lives. Yet it is for the youngest Madden sister's marriage that the novel reserves its most sinister critique. With superb detachment Gissing captures contemporary society's ambivalence towards its own period of transition. The Odd Women is a novel engaged with all the major sexual and social issues of the late-nineteenth century. Judged by contemporary reviewers as equal to Zola and Ibsen, Gissing was seen to have produced an `intensely modern' work and it is perhaps for this reason that the issues it raises remain the subject of contemporary debate.